Novel therapeutic targets for the treatment of oral cancer with compounds identified in Wrightia tinctoria: An in silico docking study with oncogenic pathways - Karuppur Thiagarajan Magesh; Deepak Chandrasekharan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Oral cancer is the sixth most common cancer worldwide. According to scientific data on oral cancer, the epidermal growth factor receptor (EGFR) and mitogen-activated protein kinase (MAPK) are two important causative pathways responsible for cellular proliferation in oral cancer. In the current research, two chemical compounds, 3-O-methyl-d-glucose and squalene, identified in Wrightia tinctoria extract, were used to study their action on the EGFR and MAPK pathways using molecular docking to prevent oral cancer progression. Materials and Methods: A molecular docking analysis was carried out based on the chemical makeup and similarities of chemicals derived from the plant with the target oncogenic proteins EGFR and MAPK. Following protein synthesis by Biovia Discovery Studio Visualizer, ligands were imported for virtual screening using PyRx, a program for computational drug discovery for the virtual screening of libraries of compounds against therapeutic targets. Results: The molecular docking investigation between 3-O-methyl-d-glucose, squalene, and the oncogenic pathways EGFR and MAPK was conducted using the Biovia Discovery Studio Client 2021 and AutoDock Vina software. In contrast to squalene, which exhibited an inhibitory constant of 44.99 µM and a ligand efficacy of 0.20, 3-O-methyl-d-glucose had an effective inhibitory constant (10.5 mM) on EGFR and MAPK. Both substances hindered the LSY721 binding site, which in turn suppressed the activity of oncogenic progression. Conclusion: 3-O-methyl-d-glucose and squalene found in W. tinctoria can inhibit the progressive activity of cancer-causing proteins (EGFR, MAPK) in oral cancer. 3-O-methyl-d-glucose was found to inhibit the oncogenic proteins more efficiently than squalene.